Legal Protection of Franchisees For Franchisor’ Actions - Jamin, Imelda; Kencanawati, Erny; Suasungnern, Sineerat (CV. Era Digital Nusantara, 2025)
This research aims to analyse the legal protection for franchisees against unlawful acts of franchisors in the context of the franchise business in Indonesia. Based on a qualitative approach with a normative analysis method, this research examines existing regulations, such as Government Regulation No. 42 Year 2007 and its amendment in Government Regulation No. 35 Year 2024, which provide a legal basis for franchisees to obtain protection against potential abuse by franchisors. The results showed that the regulation provides legal certainty and balance between the two parties by clearly regulating their respective obligations and rights. The legal protections contained in this regulation include intellectual property rights, the franchisor's obligation to provide information and training, and the obligation to include fair clauses in the franchise agreement. Although there are already supporting regulations, franchisees are expected to be more proactive in utilising their rights in accordance with applicable legal provisions. This research concludes that existing regulations are sufficient to protect the interests of franchisees, provided that they are properly implemented and complied with by all relevant parties, so as to create a healthy, fair and transparent partnership relationship in the franchise business in Indonesia.